GarÇons a la mode (1999)
Tienda de ropa en New York, USA, y en Tokyo, Japón. Diseñadas por Rei Kawakubo y por el arq. Takao Kawasaki
Keywords: ESTADOS UNIDOS; NUEVA YORK; TOKYO; JAPON; TIENDAS; INDUMENTARIA; KAWAKUBO, REI; KAWASAKI, TAKAO